Towards a global synthesis of Collembola knowledge – challenges and potential solutions - Anton Potapov; Bruno Bellini; Steven Chown; Louis Deharveng; Frans Janssens; Ľubomír Kováč; Natalia Kuznetsova; Jean-François Ponge; Mikhail Potapov; Pascal Querner; David Russell; Xin Sun; et al. (Soil Organisms, 2020)
Collembola are among the most abundant and diverse soil microarthropods, which are found in almost all (semi)terrestrial environments and often serve as model organisms in empirical studies. Diverse data collected on the biology and ecology of Collembola over the last century are waiting for synthesis studies, while developing technologies may facilitate generation of new knowledge. Collembola research in 2020 is entering the stage of global synthesis and in this opinion paper we address the main challenges that the community of collembologists is facing on this avenue. We first discuss the present status and social context of Collembola taxonomy and the potential use of novel technologies to describe new species. We then focus on aspects of community ecology, reviewing the processes of dispersal, environmental and biotic filtering, from the spatial scale of microhabitat to the globe. We also discuss the involvement of Collembola in ecosystem processes and which proxies, such as functional traits, can be used to predict the functional roles of species. Finally, we provide recommendations on how we can improve community data collection by using standard methods and better data handling practices. We call for (1) integrating morphological descriptions with high-resolution photographs and genetic barcodes for species descriptions and developing of user friendly software and machine learning approaches to facilitate deposition of structured taxonomic knowledge on web platforms; (2) multiscale studies on biodiversity distribution and community processes, especially including dispersal mechanisms; (3) recording and sharing functional, not only morphological, trait data in controlled experiments and field surveys; (4) knowledge synthesis and meta-analysis studies on the topics of ecosystem roles of Collembola, conservation of its diversity, feeding behaviour, protection mechanisms and dispersal of different Collembola species, and effects of land use and climate change on collembolan communities; (5) joint efforts in covering the gaps in Collembola knowledge, especially in underexplored regions (predominantly tropics and subtropics) using standard methodologies; (6) data sharing and its integration in open structured databases. We believe that Collembola studies could make use of new technologies and ongoing changes in society. To facilitate the progress across these research topics by 2040, we have established #GlobalCollembola, a distributed-effort community-driven initiative that aims to provide open and global data on Collembola taxonomic and genetic diversity, abundance, traits and literature and to coordinate global efforts in covering the key knowledge gaps.